Numerical Study on the Rebound of Low-Velocity Impact-Induced Indentation in Composite Laminate - Muhammad Yousaf; Chuwei Zhou (Aerospace, 2022)
Indentation is an effective indication of LVI damage in PMCs. However, indentation can rebound partly with time. Thus, a good understanding of the rebound behavior of the impacted pit is helpful in damage assessment for composites. In this paper, a transverse isotropic viscoelastic model and a viscoelastic cohesive interface model are proposed to represent the viscoelastic properties of ply and the interface between adjacent plies, respectively. In these models, we implement the in-plane 3D Hashin failure criterion to simulate ply level failures and the stress-based quadratic failure criterion and linear softening mixed-mode BK law to simulate cohesive interface failure initiation and propagation, respectively. LVI testing was performed on specimens at different impact energies (30 J, 40 J, and 50 J). Dents induced by impact will eventually rebound due to the viscoelastic behavior of plies and cohesive interfaces. This results in a decrease in depth with time. This indentation and its rebound phenomenon were simulated in ABAQUS by considering viscoelasticity with user-defined material subroutines. The simulation results show good agreement with the experimental observations and are validated accurately in terms of the indentation’s initial depth upon impact and its final rebound with time. From experiments, it was observed that the decrease in the original depth of indentation initially becomes faster with time after impact; then, it slows down with time and eventually stops due to viscoelasticity. While this decrease in the original depth of indentation remains invariable with time in simulation, it has a different rebound path.